2008
DOI: 10.1515/cclm.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

An automated assay of urinary alanine aminopeptidase activity

Abstract: We conclude that the newly developed automated assay represents a user-friendly and analytical tool to determine urinary AAP activity in a medium- to high-throughput laboratory. Potential applications include clinical diagnostic work and toxicological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Studies have shown that kidney involvement is frequent in COVID-19 patients and even acute kidney injury is common in critically ill patients (56). Our interactome analysis showed an interaction of ORF7a and nsp8 with NPEPPS, a puromycin-sensitive amino peptidase, which is commonly used as a biomarker against damaged kidneys (57). Our results also indicated the interaction of ORF7a and nsp8 with multiple proteasome-related proteins such as PSMD6, PSMD7, PSMD2, and PSMD13, which is in agreement with a previous study in which the authors revealed the interactions by overexpressing the SARS-CoV-2 gene in HEK293 cells (58).…”
Section: Resultsmentioning
confidence: 62%
“…Studies have shown that kidney involvement is frequent in COVID-19 patients and even acute kidney injury is common in critically ill patients (56). Our interactome analysis showed an interaction of ORF7a and nsp8 with NPEPPS, a puromycin-sensitive amino peptidase, which is commonly used as a biomarker against damaged kidneys (57). Our results also indicated the interaction of ORF7a and nsp8 with multiple proteasome-related proteins such as PSMD6, PSMD7, PSMD2, and PSMD13, which is in agreement with a previous study in which the authors revealed the interactions by overexpressing the SARS-CoV-2 gene in HEK293 cells (58).…”
Section: Resultsmentioning
confidence: 62%
“…They have an obvious diagnostic benefit because their measurements may provide detailed information about the nature, size and site of the damage to tubular cells and their possible necrosis or dysfunction [5]. One of these enzymes, AlaAp (EC 3.4.11.2), is an enzyme of the brush border proposed in the early seventies as a urinary marker of renal disease [6], and there is an automatic photometric assay for its determination [7]. AlaAp, together with GluAp (EC 3.4.11.7), CysAp (3.4.11.3) and AspAp (EC 3.4.11.21) are present in the renal tubular cells [8][10] and they have an aminopeptidasic function in angiotensin II metabolism, peptide that is increased in renal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of urinary enzymes and other urinary biomarkers may therefore be a valuable tool to obtain an early diagnosis during initial stages of renal disease and to follow its progression or regression, facilitating prediction of the prognosis. Urinary APs are considered promising and useful biomarkers of renal disease of different pathophysiological origin, and an automated photometric assay has been developed for their measurement [ 94 ].…”
Section: Aps As Urinary Biomarkers Of Renal Injurymentioning
confidence: 99%
“…APs activities can be readily quantified in biological samples by kinetic methods using photometric [ 94 ] or fluorometric [ 113 ] assays. Widely applied immunological techniques such as immunoblotting or ELISA can be used to analyze the amount/expression of these proteins in biological samples.…”
Section: Quantification Of Urinary Apsmentioning
confidence: 99%